Diol-functionalised benzoates as novel linkers for the formation of coordination polymers - Andrews, P.; Forsyth, C.; Fraser, B.; Junk, P.; Massi, Massimiliano; Silberstein, Morry (The Royal Society of Chemistry, 2007)
Reaction of La(HCO3)(3) with enantiomerically pure (R)-4-(2,3-dihydroxypropoxy) benzoic acid (DBAH) gives the neutral complex La(DBA)(3), which on heating undergoes self-organisation into a 1D coordination polymer, [La-2(DBA)(6)(H2O)(4)](infinity), as determined by X-ray crystallography.